Identifying of Land Suitability Sea Cucumber (Holothuria scabra) Using Geographic Information Systems and Remote Sensing Based on Physics Parameters In West Lombok - Laily Fitriani Mulyani; Marsoedi Marsoedi; Guntur Guntur (Universitas Tidar, 2019)
This study was conducted on 17th October - 27th November 2016 at Gili Asahan, Gili Layar, and Gili Gede in West Sekotong, Lombok, West Nusa Tenggara. The purpose of this study was to analyse a suitable area for sea cucumber cultivation (Holothuria scabra). Data collection had been done by survey method, acquiring primer and secondary data directly related to sea cucumber's life and analyzed by using Geographic Information System software. A physical parameters include temperature 29,14 – 30,240C, the water transparancy of the 0,78 – 1,35 m, the current speed from 0,2 to 0,7 m/s, rainfall of 174 mm, protection: protected, fairly protected and unprotected, depth 0,78 to 1,35 m, the tide of 0,9 m. Land suitability classes are determined based on the interval between the other classes S1 (40-42), S2 (37-39) and N (34-36). Based on the results of scoring that has been adapted to the class interval obtained sample points with a very appropriate category (S1) including A1, C1, C4, C5. Then for the corresponding category (S2) between the A2, A3, C2, C3. Meanwhile, according to the category is not contained in the sample points B1, B2 and B3.